Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $x$ is fixed within $[0,1]$, the limit of $n^3x^n(1-x)$ as n tends to infinity is $0$.

But how do I show this? $n^3$ tends to inifinity, but the other term tends to zero, and surely I cannot simply assume that their product tends to $0$?

And if I reason that because $x^n$ dominates $n^3$ therefore the above function tends to zero, this neglects the possibility that the function may converge to somwhere between zero and infinity.

share|cite|improve this question
up vote 2 down vote accepted

There are lots of ways to do this, but for fixed $x<1$, the only variable is $n$, and I suggest rewriting the problem as $\lim_{t\to\infty}t^3/c^t$ where $c=1/x>1$, by calling the variable $t$ instead of $n$. Then top and bottom go to infinity, and you can use L’Hospital three times to get your result. You do need to know that the derivative of $c^t$ is $\log(c)c^t$, and use the fact that the logarithm is positive.

share|cite|improve this answer

When $x = 0$ or $x = 1$ the result is obvious. If $x \in (0, 1)$ then we can easily see that $$\lim_{n \to \infty}n^{3}x^{n}(1 - x) = (1 - x)\lim_{n \to \infty}n^{3}x^{n}$$ To handle the limit of $a_{n} = n^{3}x^{n}$ I apply my favorite technique of ratio test. We have $$\lim_{n \to \infty}\frac{a_{n + 1}}{a_{n}} = \lim_{n \to \infty}\left(\frac{n + 1}{n}\right)^{3}x = x < 1$$ Hence the series $\sum a_{n}$ is convergent and therefore its $n$th term $a_{n}$ tends to zero.

If one does not have idea of series convergence and their tests then one can directly show that if $0 < \lim_{n \to \infty}a_{n + 1}/a_{n} = l < 1$ then $\lim_{n \to \infty} a_{n} = 0$. Clearly we can take a number $c$ such that $l < c < 1$ and then we know that there exists a positive integer $m$ such that $0< a_{n + 1}/a_{n} < c$ for all $n \geq m$ (use the $\epsilon$ definition of limit with $\epsilon = c - l > 0$). Then we get $$0 < \frac{a_{m + p}}{a_{m}} = \frac{a_{m + 1}}{a_{m}}\cdot \frac{a_{m + 2}}{a_{m + 1}}\cdots \frac{a_{m + p}}{a_{m + p - 1}} < c^{p}$$ Letting $p \to \infty$ and noting that $0 < c < 1$ we see that $\lim_{p \to \infty}a_{m + p}/a_{m} = 0$ and then $\lim_{p \to \infty}a_{m + p} = 0$ or what is the same as $\lim_{n \to \infty}a_{n} = 0$.

Another point which I gather from your question is about thinking of limit evaluation by "evaluation in parts". Like if two functions tend to limits $A$ and $B$ then their product tends to $AB$. This is a valid approach only when $A, B$ exist. Usually when one encounters a limit where evaluating part by part does not help (due to the fact that one of the parts does not tend to a finite limit) then we need to think a bit deeper.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.